2016
DOI: 10.18203/2394-6040.ijcmph20163357
|View full text |Cite
|
Sign up to set email alerts
|

Random blood sugar levels and pseudocholinesterase levels their relevance in organophosphorus compound poisoning

Abstract: INTRODUCTIONOrganophosphorus and organocarbamate compounds are used as agricultural and household insecticides and in the eradication of animal ectoparasites and human lice infestations. Of the various substances used for suicidal attempts in India, organophosphates and organocarbamates form a majority group. Estimation of plasma cholinesterase (pseudo cholinesterase) has an advantage because the measurement is simpler and more accurate than estimation of erythrocyte cholinesterase.1,2 In acute poisoning, mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…However greatest levels of suppression (<500 U/L) were found in 9 patients, all of whom had severe grade of poisoning with 4 out of 9 having hyperglycemia at admission. This correlated with the findings of the study conducted by Rao et al 7 A prospective observational study was carried out in Cuttak, by Rachita et al, to assess the glycemic status of OP poisoned patients. 8 It concluded that a fall in serum cholinesterase value was more pronounced in patients having RBS >140 mg%, in parallel with severity of poisoning.…”
Section: Rbs-classifiedsupporting
confidence: 87%
See 1 more Smart Citation
“…However greatest levels of suppression (<500 U/L) were found in 9 patients, all of whom had severe grade of poisoning with 4 out of 9 having hyperglycemia at admission. This correlated with the findings of the study conducted by Rao et al 7 A prospective observational study was carried out in Cuttak, by Rachita et al, to assess the glycemic status of OP poisoned patients. 8 It concluded that a fall in serum cholinesterase value was more pronounced in patients having RBS >140 mg%, in parallel with severity of poisoning.…”
Section: Rbs-classifiedsupporting
confidence: 87%
“…An observational study of 50 patients was conducted by Rao et al, in Hyderabad, to study the relevance of RBS levels in acute OP poisoning. 7 They concluded that hyperglycemia at admission was commoner than expected, in cases with moderate to severe poisoning. Hyperglycemia at admission correlates with depression of pseudocholinesterase levels in OP poisoning.…”
Section: Rbs-classifiedmentioning
confidence: 97%
“…At the time of admission, a patient's glycemic status may help determine the severity of OPC. Also Rao and Raju, (2016) discovered that levels of glucose greater than 200 mg/dl were reliable parameters for predicting mortality and the need for ventilator support, and that hyperglycemia on admission was correlated with the severity of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…found that there was a rise in the random blood glucose with increase in severity and blood glucose status at time of admission may help in identifying the severity of poisoning. Rao and Raju, (2016) [29] . found that elevated blood glucose at the time of admission linked well with severity of cases and levels of RBS more than 200 mg/dl were fair parameters to guess mortality and the need for ventilatory support.…”
Section: Discussionmentioning
confidence: 99%